Oviposition antixenosis in common bean varieties to Bemisia tabaci (Hemiptera: Aleyrodidae) Middle East-Asia Minor 1 (MEAM1) and Spodoptera frugiperda (Lepidoptera: Noctuidae) (Research, Society and Development, 2025)
Brazil, the world’s third-largest producer of beans, faces considerable challenges in cultivating this essential crop, which is primarily consumed domestically. Bean production is often threatened by pest insects, particularly the whitefly Bemisia tabaci MEAM1 (Gennadius) and the fall armyworm Spodoptera frugiperda (J. E. Smith), both of which can reduce yields and impair grain quality. Alternative management strategies, such as the use of resistant varieties, represent promising tools for controlling these pests while minimizing chemical inputs. This study aimed to identify bean varieties exhibiting resistance through antixenosis, a resistance category in which plants are less attractive for feeding or oviposition. In the first experiment, whitefly oviposition was evaluated in two groups of bean varieties. Group A included Dobalde, BRS Esplendor, IAC Esplendor, IAC Milênio, and IAC Formoso, while Group B included Dobalde, BRS Esplendor, IAC Una, IAC Alvorada, and Cavalo BRPR. The results showed that Dobalde and IAC Alvorada were less preferred for whitefly oviposition, whereas higher egg numbers were recorded on IAC Una, IAC Milênio, BRS Esplendor, and Cavalo BRPR. A second experiment assessed S. frugiperda oviposition using four varieties selected from the first test (Dobalde, IAC Milênio, Cavalo BRPR, and IAC Una), but none exhibited resistance to this pest. Trichome density was also measured, with no significant differences observed among varieties. Overall, the results indicate that the Dobalde variety demonstrated antixenosis-based resistance to B. tabaci, whereas no bean variety showed resistance to S. frugiperda.